The role of electronic service and pricing in attracting customers (A field study on the Sudanese banking sector) - Hassan, Elham Ezeldeen; Saeed, Naamat Muhammad (Journal of Economic, Administrative and Legal Sciences, 2020)
The study dealt with the relationship of electronic service and electronic pricing in attracting customers by applying to the Sudanese banking sector The problem of the study lies in identifying the relationship between electronic service and electronic pricing in attracting customers by identifying the quality of the correlation between electronic service and electronic pricing and attracting customers and the importance of the study stemmed from The big role that banks play in providing financial services in Sudan and through information and data and analyzing them to benefit from them, and the main goal of this study is to try to reveal the impact of electronic marketing My clients in the bank attract, the study seeks to test the following hypotheses of the study, there is a strong positive correlation with statistical function between the electronic service and attract customers, and there is a positive correlation relationship with a medium statistical function between the electronic pricing and attract customers. The study followed the historical approach, deductive approach, descriptive approach and inductive approach, the study reached a number of results, the most important of which is that providing good electronic service is no longer optional or a set of slogans and methods of advertising but rather has become a reality imposed by the nature of conditions and variables in the contemporary business environment as imposed by the nature and characteristics of clients themselves, the basis To achieve success, growth and continuity in the market depends on the presence of a customer base and the strengthening of the relationship between customers and the bank, and one of the most important recommendations recommended by the study is the establishment of sections for electronic banking services in the bank’s branches and the establishment of an ester Tejah marketing is working to attract more of both cases, customers continuity in the creation of the bank's branches and improve the work, the use of modern software in the electronic service to keep pace with technological developments, taking into account security and safety in the payment of the amounts of buying and selling via computer networks because of concerns arising from the possibility of interception and theft.
Keywords: electronic service; electronic pricing; attracting customers